Pakanta in the Lithuanian Worldview - Smetonienė, Irena (Lietuvių kalba, 2024)
Pakanta (acceptance) is a sociological, psychological, philosophical, and even political term. Culture researchers focus on cultural elements, religious studies discuss tolerance towards specific religious communities, and philosophers, alongside tolerance, also refer to respect. Together, these concepts form the content of tolerance. The Latin word tolerantia and the Lithuanian word pakanta have the same origin, both stemming from the concept of patience. However, these terms are not entirely synonymous. Pakanta is a concept of everyday consciousness, while tolerancija is a category in philosophy and ethics. Thus, the concept of pakanta evokes interests of representatives from various fields, but linguistically it has not been widely studied. The aim of this article is to discuss the lexical meanings of pakanta in Lithuanian dictionaries, investigate how the term is used in public media texts, and examine how young people respond to the question, “What does pakanta mean to you?” In Lithuanian lexicographical sources, the lexemes pakanta and tolerancija are presented as synonyms. Illustrative examples show that pakanta is most often associated with patience. Pakanta has limits, and tolerating things that harm societal welfare should turn into intolerance. Although rarely using the term, young people primarily associate it with patience—this lexeme appears in half of the responses to the question “What does pakanta mean to you?”. The concept of tolerancija (tolerance) is more familiar and understood without explanation, appearing in 48% of the responses. As in lexicographical sources, both lexemes are used as synonyms. In media texts, pakanta and tolerancija are used either as synonyms or as equivalent concepts. From the collected examples, it is evident that the concept of pakanta in Lithuania also includes the respect mentioned by philosophers. Pakanta can apply not only to people or living things, but also to inanimate objects (such as food, medicine, taste, etc.). In media texts, the semantic aspects of intolerance—nepakanta—are particularly emphasised. Intolerance also has two sides: the positive one, as the inability to tolerate universal violations of order or various negative phenomena that may harm society or even the state; and the negative one, when it arises from envy and manifests itself as contempt for those who think differently, earn more, or have different orientations. Intolerance in the studied material further highlights the shades of pakanta. The use of pakanta is decreasing not only among young people but also among other Lithuanians, with tolerancija taking its place. The study leads to the conclusion that the cognitive definition of pakanta includes patience, self-control, respect.
Keywords: acceptance; tolerance; respect; patience